Tend to one's own house: The effect of firm CSR on employee effort - Douthit, Jeremy; Mao, Zhiping (Kyle); Martin, Patrick (Contemporary Accounting Research, 2024)
Abstract We examine whether a firm's corporate social responsibility (CSR) actions that benefit external parties can cause the firm's employees to reduce their effort. We expect employees will reduce their effort in response to their firm's external CSR actions when they perceive that they are treated poorly by the firm and that the firm's external CSR actions use resources that could have been readily transferred toward improving employee treatment. We expect that, when employees hold both of these perceptions, they will react negatively to the firm's CSR actions due to heightened feelings of unfairness. Results support our expectations and theory. We find that employees respond negatively to CSR only when they perceive that they are treated poorly by their firm and that CSR uses transferable resources. Further, we find these effects are driven by employees' perceptions of the fairness of their firm's actions toward employees. Our study suggests that firms should consider how employees perceive their treatment by the firm and the transferability of the resources used for CSR actions that benefit external parties.